A concept of a supercritical CO2 Brayton and organic Rankine combined cycle for solar energy utilization with typical geothermal as auxiliary heat source: Thermodynamic analysis and optimization. (November 2022) - Cao, Yue; Li, Peiyu; Qiao, Zongliang; Ren, Shaojun; Si, Fengqi
Abstract: This paper presents an investigation of a supercritical CO2 Brayton and organic Rankine (sCO 2 -ORC) combined cycle for solar energy utilization. This combined cycle uses typical geothermal as auxiliary heat source to enhance its thermodynamic performance. Organic working fluid is preheated by supercritical carbon dioxide, which absorbs heat from solar power tower and then expands in a turbomachinery. Then geothermal source enhances the grade of organic working fluid before it expanded. A solution procedure is proposed to estimate the thermodynamic performance of this combined cycle. Results show that the recompression sCO 2 -ORC combined cycle has the best thermodynamic performance when using CO2 - enhanced geothermal system (EGS) as auxiliary heat source. The most suitable organic working fluid for CO2 -EGS is R245ca. Genetic algorithm optimization indicates that the optimal thermal efficiency and net power of the combined cycle is 35.07% and 16.63 MW, respectively, whose decision variable of split ratio is 0.559. Findings suggest that the sCO 2 -ORC combined cycle has a thermodynamic advantage utilizing the solar energy and auxiliary geothermal energy. Highlights: A sCO2 -ORC combined cycle for solar energy utilization was studied. This combined cycle was coupled with typical geothermal as auxiliary heat source. The recompression sCO2 -ORC combined cycle with CO2 -EGS performed better. R245ca was the most suitable organic fluid for CO2 -EGS auxiliary heat. GA optimization showed this combined cycle had advantage over thermodynamic performance.